Development of an engine control module and dashboard display based on electric vehicle system - Low, Alex Boon Hwee (2014)
This project involves the design and building of an electric vehicle based on the Honda S2000 convertible. Along the design process, numerous changes have been made to incorporate new features such as conversion to a 4 seater sedan, inclusion of battery packs, wireless charging features and such. With the modifications involved, the original S2000 on board systems have to be revised and changed as accordingly.